Nuclear markers support the mitochondrial phylogeny of Vipera ursinii–renardi complex (Squamata: Viperidae) and species status for the Greek meadow viper - Mizsei, Edvárd; Jablonski, Daniel; Roussos, Stephanos A.; Dimaki, Maria; Ioannidis, Yannis; Nilson, Göran; Nagy, Zoltán T. (Zootaxa, 2017)
Meadow vipers (Vipera ursinii–renardi complex) are small-bodied snakes that live in either lowland grasslands or montane subalpine-alpine meadows spanning a distribution from France to western China. This complex has previously been the focus of several taxonomic studies which were based mainly on morphological, allozyme or immunological characters and did not clearly resolve the relationships between the various taxa. Recent mitochondrial DNA analyses found unexpected relationships within the complex which had taxonomical consequences for the detected lineages. The most surprising was the basal phylogenetic position of Vipera ursinii graeca, a taxon described almost 30 years ago from the mountains of Greece. We present here new analyses of three nuclear markers (BDNF, NT3, PRLR; a first for studies of meadow and steppe vipers) as well as analyses of newly obtained mitochondrial DNA sequences (CYT B, ND4).Our Bayesian analyses of nuclear sequences are concordant with previous studies of mitochondrial DNA, in that the phylogenetic position of the graeca clade is a clearly distinguished and distinct lineage separated from all other taxa in the complex. These phylogenetic results are also supported by a distinct morphology, ecology and isolated distribution of this unique taxon. Based on several data sets and an integrative species concept we recommend to elevate this taxon to species level: Vipera graeca Nilson & Andrén, 1988 stat. nov.